Hypoxanthine-guanine phosphoribosyltransferase and inosine 5′-monophosphate dehydrogenase activities in three mammalian species: aquatic (Mirounga angustirostris), semi-aquatic (Lontra longicaudis annectens) and terrestrial (Sus scrofa) - Barjau Perez-Milicua, Myrna; Zenteno-Savin, Tania; Crocker, Daniel E.; Gallo, Juan P. (Frontiers in Physiology, 2015)
Aquatic and semiaquatic mammals have the capacity of breath hold (apnea) diving. Northern elephant seals (Mirounga angustirostris) have the ability to perform deep and long duration dives; during a routine dive, adults can hold their breath for 25 min. Neotropical river otters (Lontra longicaudis annectens) can hold their breath for about 30 sec. Such periods of apnea may result in reduced oxygen concentration (hypoxia) and reduced blood supply (ischemia) to tissues. Production of adenosine 5’-triphosphate (ATP) requires oxygen, and most mammalian species, like the domestic pig (Sus scrofa), are not adapted to tolerate hypoxia and ischemia, conditions that result in ATP degradation. The objective of this study was to explore the differences in purine synthesis and recycling in erythrocytes and plasma of three mammalian species adapted to different environments: aquatic (northern elephant seal) (n=11), semiaquatic (neotropical river otter) (n=4) and terrestrial (domestic pig) (n=11). Enzymatic activity of hypoxanthine-guanine phosphoribosyltransferase (HGPRT) was determined by spectrophotometry, and activity of inosine 5’-monophosphate dehydrogenase (IMPDH) and the concentration of hypoxanthine (HX), inosine 5’-monophosphate (IMP), adenosine 5’-monophosphate (AMP), adenosine 5’-diphosphate (ADP), ATP, guanosine 5’-diphosphate (GDP), guanosine 5’-triphosphate (GTP), and xanthosine 5’-monophosphate (XMP) were determined by high-performance liquid chromatography (HPLC). The activities of HGPRT and IMPDH and the concentration of HX, IMP, AMP, ADP, ATP, GTP and XMP in erythrocytes of domestic pigs were higher than in erythrocytes of northern elephant seals and river otters. These results suggest that under basal conditions (no diving, sleep apnea or exercise), aquatic and semiaquatic mammals have less purine mobilization than their terrestrial counterparts.